Dig a bit deeper. Law, regulation and the illicit antiquities market - Mackenzie, Simon R. M. (The British journal of criminology, 2005)
The UK market in antiquities is the site of trade of an unknown number of illicit artefacts. These illicit antiquities are often the product of looting in underdeveloped nations. The UK has recently passed a new statute criminalizing the knowing purchase of a looted cultural object. The statute, however, is likely to have little effect on the trading practices of London's antiquity dealers, due to peculiarities of their style of transacting, which will be examined here. This paper is therefore (a) a study of an illicit market which is still in the early stages of a slow move from non-criminal to criminal, as its destructive tendencies are increasingly brought to public and official recognition and (b) yet another note of warning to regulators who feel that, on the implementation of a token criminal prohibition, markets will sanitize themselves